A questionnaire based cross sectional study of the knowledge, attitude and practice of pharmacovigilance among the health care professionals in a tertiary care teaching hospital in upper Assam, India - Gohain, Swapnanil; Aziz, Sahid; Chaliha, Meghali (International Journal of Research in Medical Sciences, 2019)
Background: Adverse drug reactions (ADR) are one of the major reason of morbidity, mortality and increase in health-care costs. The pharmacovigilance programme of India (PvPI) encourages the active participation of all health care professionals (HCP) in reporting suspected ADR to ensure enhanced patient safety. But present statistics shows under reporting of suspected ADR. So, this study was undertaken with the objectives of assessing knowledge, attitude and practice (KAP) of pharmacovigilance among the HCP and to evaluate various reasons of under reporting of suspected ADR. Methods: This is a cross-sectional observational study of knowledge, attitude and practice (KAP) of HCP including faculties, resident doctors and postgraduate trainee (PGT), internship doctors and nurses on pharmacovigilance; conducted at department of Pharmacology, Jorhat Medical College and Hospital(JMCH). The pretested and peer reviewed questionnaire was distributed among 150 HCP and the responses were collected after one day. Data were analyzed using MS-excel software and was expressed in percentage. Results: Out of 150 questionnaires, 118 responses were received (32 faculties, 27 PGT, 38 internship doctors and 21 nurses). Good knowledge (78.4%) and fair attitude was found among the HCP but there was lack of practice of pharmacovigilance due to reasons mainly non availability of suspected ADR reporting form (27.1%), didn’t think reporting was necessary (34%), fear of consequences (16.1%) and lack of awareness (16.1%) among others. Conclusions: Good attitude was observed among HCP. With proper measures like sensitization and educational intervention ADR, reporting may be improved in the future.